In vitro propagation of purple pitahaya (Hylocereus costaricensis [F.A.C. Weber] Britton & Rose) cv. Cebra - Viñas Meneses, María (2012)
Limitations to large-scale propagation of purple pitahaya (Hylocereus costaricensis [F.A.C. Weber] Britton & Rose), a potential source of betalains for the food industry, can be overcome through utilization of in vitro culture technologies. In this work, successful in vitro propagation from areoles of adult purple pitahaya plants is reported. Factors affecting culture initiation, bud sprouting and growth, shoot multiplication, rooting, and acclimatization were studied. Best results for culture initiation were obtained from the central region of new joints by disinfection of large (5–7 cm in length) explants that were subsequently divided. Explants were sequentially treated with Extran® alkaline detergent for 10 min, followed by immersion in 70 % (v/v) ethanol for 15–30 s, a mixture of the fungicide Benomyl and the bactericide Agrymicin (2 g l−1 each) for 30 min, and disinfection in sodium hypochlorite (1.0 % w/v) for 15 min. Culture of sectioned individual areoles, without removing thorns, on Murashige and Skoog medium supplemented with 15 or 30 μM N 6-benzylaminopurine (BAP) for 3 mo with monthly subcultures, followed by transfer to the same medium with reduced BAP (0–2 μM), induced bud sprouting in over 80 % of explants, adequate growth of the shoots, with production of lateral shoots, and spontaneous rooting within 160 d. These plants were successfully acclimatized in vermiculite and peat moss (1:1), or perlite and peat moss (2:1) in the greenhouse, with over 90 % survival rate. One hundred percent of the in vitro-derived plants were successfully transferred to the field. Furthermore, these plants showed higher survival rates, larger height and increase in stem diameter than equivalent plants from the same genotype, derived from stem segments (the common clonal propagation system utilized for this species) that were simultaneously planted.